Effects of the application of pregerminative stimulants and different types of substrates, in the germination of Gmelina arborea Robx seeds, in the nursery stage (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The objective of this research project was to analyze the effects of theapplication of pregerminative stimulants and different types ofsubstrates in the germination of Gmelina arborea, in the nursery stage.For the application of the project, 3.5 pounds of melina seeds werepurchased to which the respective pregerminative treatment wasapplied, prior to the sowing of the same ones, establishing a total of1,440 seeds in 36 tubes of 40 seeds per tube. With three repetitions,three pregerminative treatments were used (nitric acid and distilledwater, hot water and cold water) on G. arborea Robx seeds, with threecombined substrates (orchard soil + sand, common soil + UTEQ fertilizer,common soil + rice husk), plus the control to which no treatment wasapplied, since it served as a control, but it was sown on combinedsubstrates. After two weeks of germination data collection, the growthvariables were measured during 8 weeks of height, number of leaves,stem diameter, length and width of the leaf and length of the root, thelatter only once. The work was carried out in the experimental farm "LaRepresa" owned by the State Technical University of Quevedo. Thepregerminative treatments applied to Gmelina arborea Robx seeds,varied in differences on germination between treatments, in addition tothe different combined substrates in which it was put to germinate,differences were evidenced in how many growth variables. Giving us asresults several similarities between treatments and substrates.